Respostas

2013-12-14T09:06:16-02:00
Faz por parte : (2/3 - 1/2)²

2² / 3² - 1² / 2² ~> { 4 /9 - 1 / 4 } mmc = 36

36 : 9 x 4 = 16
36 : 4 x 1 = 9            

        { 4 /9 - 1 / 4 } ~> 16 - 9 / 36 =  { 7 / 36 }

agora com o outro

(- 1/2 + 1/3)²  = -1² / 2² + 1² / 3² ~> {1 /4 + 1/ 9 } mmc = 36

36 : 4 . 1 = 9
36: 9 . 1 =  4

 {1 /4 + 1/ 9 } = 9+4 / 36 = { 13 / 36 }

pronto : { 7 / 36 } : { 13 / 36 }  < divisão com fração , repete a primeira e multiplica pelo inverso da segunda .

7 / 36 x 36 /13 = 7 /13

ou seja : 2/3 - 1/2)² ÷ (- 1/2 + 1/3)² = 7 /13






1 5 1
2013-12-14T09:58:16-02:00
(4/9-1/4)÷ (-1/4+ 1/9)
(4/36-9/36) X (-4/1+9/1)
-5/36 X 13= -65/36




1 1 1